Lung cancer resection in octogenarian patients - Spaggiari, Lorenzo; Petrella, Francesco; Maione, Paolo; Gridelli, Cesare (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
According to the World Health Organization (WHO), life expectancy at birth reflects the overall mortality level of a population, summarizing the mortality pattern that prevails across all age groups in a given year—children and adolescents, adults and the elderly (1).